Cholinergic responses of seminal vesicles isolated from rats exposed perinatally to hydrocortisone - Pereira, OCM; Yasuhara, F.; Arena, A. C. (Elsevier B.V., 2003)
This study was performed in order to investigate the cholinomimetic response of seminal vesicles isolated from rats treated with hydrocortisone acetate during perinatal life. At the adult phase, the body weight and the wet weight of the seminal vesicle of these animals were unchanged. However, these male rats exhibited a significant reduction in plasma testosterone concentration. A significant increase in the sensitivity of the seminal vesicle to acetylcholine was also observed. Despite this, there was a significant reduction in the maximum contractile response of the organ to this transmitter. These results indicate that exposure to hydrocortisone during the critical period of brain sexual differentiation has a long-term effect on testosterone production of male rats. In addition, physiological levels of cortisone in perinatal life are also essential to support the contractile response pattern of the seminal vesicle to acetylcholine in adult life, probably crucial to the reproductive process. (C) 2003 Elsevier B.V. Ltd. All rights reserved.
Keywords: hydrocortisone; acetylcholine; acetyl-beta-methylcholine; seminal vesicle; rat